Ecological bases of formation of the land use of the territories of the natural reservoir fund in the composition of ecological network of Ukraine - Hetmanchik, I.; Hunko, L.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2018)
The article highlights ecological and economic measures on the formation of land use territories of the nature reserve fund within the ecological network of Ukraine, its current state and problems, as well as directions of improvement. These measures are directed towards the balanced provision of the needs of the population and sectors of the economy with land resources, rational use and protection of lands, preservation of landscape and biodiversity, creation of environmentally safe living conditions of the population and economic activity and protection of land from depletion, degradation and pollution. Key words: ecological network, landscape, natural reserve fund, sustainable land use, biota.